Rubbing and drawing: generic ways to improve the thermoelectric power factor of organic semiconductors? - Scheunemann, Dorothea; Vijayakumar, Vishnu; Zeng, Huiyan; Durand, Pablo; Leclerc, Nicolas; Brinkmann, Martin; Kemerink, Martijn (Advanced electronic materials, 2020)
Highly oriented polymer films can show considerable anisotropy in the thermoelectric properties leading to power factors beyond those predicted by the widely obeyed power law linking the thermopower S and the electrical conductivity σ as S ∝ σ−1/4. This has led to encouraging practical results with respect to the electrical conductivity, notwithstanding that the conditions necessary to enhance σ and S simultaneously are less clear. Here, kinetic Monte Carlo simulations are used to study the impact of structural anisotropy on the thermoelectric properties of disordered organic semiconductors. It is found that stretching is a suitable strategy to improve the conductivity along the direction of strain, whereas the effect on the power factor depends on the morphology the polymer crystallizes. In general, crystalline polymers show a simultaneous increase in σ and S which is not the case for amorphous polymers. Moreover, it is shown that the trends resulting from simulations based on variable-range hopping are in good agreement with experiments and can describe the different functional dependencies in the S versus σ behavior of different directions.
First published: 14 July 2020
Gesehen am 12.11.2021